4x+13-2x+13=-4

Simple and best practice solution for 4x+13-2x+13=-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+13-2x+13=-4 equation:



4x+13-2x+13=-4
We move all terms to the left:
4x+13-2x+13-(-4)=0
We add all the numbers together, and all the variables
2x+30=0
We move all terms containing x to the left, all other terms to the right
2x=-30
x=-30/2
x=-15

See similar equations:

| h/2+8=11 | | -(4y+5)-(3y-7)=-4 | | -x+21+3x+21=6 | | 1/4x=67 | | 7a+64a+64=0 | | s-$15=$15.19 | | 10-x-x^2=7 | | 8x-x=2x-80 | | -5x-2x=1 | | b-78/3=6 | | 5x+7-2(x+5)=x-10+2(x-3) | | x²+2x-24=0 | | 23-4r=11 | | 25x+12=10-8 | | 13(c+1)=13 | | h–1.8=3.2 | | -16s+-8s+-15=9 | | -(6x/5)+5=35 | | q/3-1=3 | | 6x+20=8x+90 | | -a/5-12=10 | | 5-(2x+4)=13 | | 12+v=8 | | 15k+-17k=-20 | | 250(0.25)+0.2x=(250+x)(0.3) | | 4j+-5j=6 | | 5.{2x+4}=30 | | 2x+3/10+4x-1/10=3/10 | | 6a-7+2=—23 | | 2x+3(x-1)=4x+6 | | -2x+13+3x=2+x+11 | | 2{x+1}=12 |

Equations solver categories